Asymptotic Model Matching for LPV Systems. Issue 26 (2018) - Conte, G.; Perdon, A.M.; Zattoni, E.
Abstract: We consider the problem of forcing the output of a given Linear Parameter Varying (LPV) plant to match asymptotically that of a given LPV model using a static or a dynamic feedback control law that also quadratically stabilizes the plant. The problem is investigated from a structural point of view and solvability conditions are expressed in geometric terms. Under suitable hypotheses, checkable sufficient conditions and viable procedures for constructing solutions are provided.